External collaboration of open innovation and financial performance of SMES in Tamaulipas, Mexico - Alvarez-Aros , Erick Leobardo (2022)
Open innovation is a collaborative paradigm that improves business performance. However, the majority of investigations approach large and multinational companies with developed economies, so this work analyzed the relationship of external collaboration of open innovation with financial performance in small and medium-sized companies in an emerging economy. For this, a questionnaire was applied to owners and managers of 145 companies located in Tamaulipas, Mexico. The results processed through structural equations in SPSS and AMOS indicate the absence of a positive and significant relationship between the vertical collaboration of open innovation (customers, users and suppliers) and financial performance. In contrast, a positive and significant relationship was found between the horizontal collaboration of open innovation (educational institutions, government and competitors) with financial performance, with elements such as co-development of products, inputs of knowledge and ideas, acquisition of machinery, equipment, software and supplies.